A review on leguminous cover crop and its effect on soil nitrogen and phosphorus / Husni Mubarak Mohamad Yaakob - Mohamad Yaakob, Husni Mubarak (Faculty of Plantation and Agrotechnology, 2016)
This paper reviews the effect of planting leguminous cover crop on the status of soil Nitrogen and Phosphorus. The most common legumes crop planted in the Oil palm and Rubber plantation in Malaysia were Calapogonium Mucunoides, Centrosema Pubescene, Pueraria javanica Mimosa pudica, Pueraria phaseoloides, Arachis pintoi and Mucuna bracteata. In general, planting cover crops will improve soil nitrogen and Phosphorus. Mucuna pruriens recorded the highest nitrogen fixation in soil (0.29%). For soil Phosphorus, Mimosa invisa recorded highest phosphorus concentration in the soil followed by Calapogonium mucunoides, Mucuna pruriens, Crotalaria juncea and Pueraria javanica. Therefore, combination of planting/intercropping Mucuna Pruriens and Calapogonium mucunoides is recommended to improve soil nitrogen and phosphorus.